UNSYNCHRONIZED IMPACT OF LEGAL REGULATION ON THE LOSS OF STATE’S STANDING FOR THE PREFERENCE RIGHT OF TAX DEBT IN BANKRUPTCY - Ratih Damayanti; Fitriani Abdi (Universitas Negeri Semarang, 2020)
The state has a preference right (priority) to collect tax debts on goods which belong to the taxpayer (debtor), meaning that the state's position as a preferred creditor is declared to have advance rights to the taxpayer's property to be auctioned in public. Preference rights by the State for paying off tax debts are in fact not as easy as imagined, there are disharmony in several laws and regulations, namely between the Taxation, Bankruptcy and Labor Laws and the Constitutional Court Verdict No.67/PUU-IX /2013 and other problems that affect the State's pre-emptive rights over paying tax debts. The objective of this study is to determine the impact of disharmony of Legal Regulations relating to Debt Repayment in Bankruptcy Against the State's Standing on Preferential Rights of Tax Debt. Based on research, the position of laborers' wages in Constitutional Court Decision No. 67/PUU-XI /2013 contrary to the provisions of the KPKPU Code which regulates labor wages as a bill of general preferred creditors and based on the principle of lex posteriori derogat legi priori, the position of laborers' wages in bankruptcy is based on the provisions of the KPKPU Code which overrides the provisions of Code No. 13 of 2013. Second, the consideration of the Constitutional Court on Verdict No. 67/PUU-XI/2013, is not in same direction with the provisions of the KPKPU Code which regulates that the wages of workers owed both before and after the bankruptcy was declared is a bankruptcy debt.